Approach to the acutely dyspnoeic cat. Issue 2 (5th March 2021) - Borgeat, Kieran; Pack, Matthew
Abstract : Background : Dyspnoea, defined as difficult or laboured breathing, is a common feline presentation in primary care practice. Early clinical signs may be difficult for owners to identify at home and often dyspnoeic patients worsen with travel‐associated stress. As such, many cats first present to vets with severe respiratory distress. Acute cases are a diagnostic challenge due to the fragile and unstable nature of the patient. Aim of the article : This article describes how to strike a balance between the interventions that are required to stabilise an individual and achieve a diagnosis, while avoiding further deterioration by not doing too much too soon.